Are fish sensitive to trawling recovering in the Northeast Atlantic?. Issue 10 (5th July 2020) - Rindorf, Anna; Gislason, Henrik; Burns, Finlay; Ellis, Jim R.; Reid, David
Abstract: The protection of sensitive species from overfishing is a key aspect of the ecosystem approach to fisheries management. We use life‐history parameters and knowledge of fish shape and habitat to estimate the sensitivity of 270 species in the Northeast Atlantic to demersal trawling and compare sensitivity to the most recent IUCN categorization. Species classified as threatened were on average significantly more sensitive to trawling than other species. Using trawl surveys in European Atlantic waters from 36°N to 62°N, we estimated indicators of abundance of 31 highly sensitive species and compared changes in abundance to sensitivity, management measures, and value of landings. The abundance of 23 of the 31 sensitive species increased after year 2000 with 14 of the species showing increases significant at the 5% level. The increases were not due to specific management measures, as less than half of the species were covered by catch limits. Furthermore, sensitivity or value of landings was not related to trends in abundance. Three species (Atlantic wolf‐fish, tusk and starry ray) declined significantly. These species are all at their southern distributional limit in the North Sea. Synthesis and applications . We recommend monitoring the development of sensitive species to identify species under pressure and allow rapid management actions before species enter the IUCN threatened category. Furthermore, we recommend taking precautions where species are under combined pressure from climate change and fishing. Abstract : We recommend monitoring the development of sensitive species to identify species under pressure and allow rapid management actions before species enter the IUCN threatened category. Furthermore, we recommend taking precautions where species are under combined pressure from climate change and fishing.